Antiviral activity of Ladania067, an extract from wild black currant leaves against influenza A virus in vitro and in vivo - Haasbach, Emanuel; Hartmayer, Carmen; Hettler, Alice; Sarnecka, Alicja; Wulle, Ulrich; Ehrhardt, Christina; Ludwig, Stephan; Planz, Oliver (Frontiers in Microbiology, 2014)
Influenza, a respiratory disease caused by influenza viruses, still represents a major threat to humans and several animal species. Besides vaccination, only two classes of drugs are available for antiviral treatment against this pathogen. Thus, there is a strong need for new effective antivirals against influenza viruses. Here, we tested Ladania067, an extract from the leaves of the wild black currant (Ribes nigrum folium) for potential antiviral activity against influenza A virus in vitro and in vivo. In the range of 0 - 1mg/ml the extract showed no cytotoxic effect on three cell lines and a CC50 of 0.5 ± 0.3 mg/ml, on PBMCs. Furthermore, the extract did not influence the proliferative status of human lymphocytes. In contrast, Ladania067 was highly effective (EC50 value: 49.3 ± 1.1 ng/ml) against the human pandemic influenza virus strain A/Regensburg/D6/09 (H1N1). The extract exhibited an antiviral effect when the virus was pre-incubated prior to infection or when added directly after infection. No antiviral effect was found when infected cells were treated 2, 4 or 8 h after infection, indicating that Ladania067 blocks a very early step in the virus infection cycle. In the mouse infection model we were able to demonstrate that an intranasal application of 500 µg Ladania067 inhibits progeny virus titers in the lung up to 85% after 24 h. We conclude that the extract from the leaves of the wild black currant may be a promising source for the identification of new molecules with antiviral functions against influenza virus.